DILAN (DETEKSI DINI-LANJUT) NARKOBA PELAJAR SMPN-3 KECAMATAN CEMPAKA KOTA BANJARBARU - Marlinda, Evy; Firdaus, Syamsul; Haitami, Haitami (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2022)
Drug abuse in students are increase. Banjarbaru City shows 305 case drug abuse in 65% students in the range 10-19 years old covers third highest district are Cempaka district, Landasan Ulin district and Banjarbaru district. Objective : supportive knowledge early teenage traits of drug abuser, how to prevent drug abuse by reinforcement of assertive behavior and self concept. Method : screening drug abuse randomly to 100 students,  leaflet distribution, practical simulation and health education to 55 participants of community school. Result : urine test to 95 students show negative, health promotion by DILAN drug abuse shows difference between pre and post test. Training introduction of DILAN drug abuse will help community school to care with drug abuse. Getting early to know potential deviation will be easy to early detection and prevention by teacher and family in school level. Recommendation : the need to continuity of program by monitoring aplication and tools by online program. Keyword : early detection, drug abuse, students